(untitled) (Práxis Educativa, 2024)
In this article, the institute of sentence remission through reading is analyzed, especially the potential of reading practiced in a critical, dialogical way, aiming at autonomy and freedom for people deprived of liberty due to electronic monitoring. Prepared through bibliographical and documentary research, and an experience report on the Asas à Leitura [Wings to Reading] Extension Project (carried out in Pelotas, Rio Grande do Sul, Brazil), the intention is to demonstrate that reading carried out by people deprived of liberty from a contesting viewpoint, in a Freirean perspective, can contribute to the weakening of criminal subjection and punitive subjectivities. In doing so, it enables liberation from the vicious circle of political, social and economic processes that engender criminalization and sustain the phenomenon of mass incarceration. Keywords: Sentence remission through reading. Education. Prison System. Criminology.